The Effect of IL-6 Inhibitors on Mortality Among Hospitalized COVID-19 Patients: A Multicenter Study. (20th November 2020) - Sinha, Pranay; Jafarzadeh, S Reza; Assoumou, Sabrina A; Bielick, Catherine G; Carpenter, Bethanne; Garg, Shivani; Harleen, Sahni; Neogi, Tuhina; Nishio, Midori Jane; Sagar, Manish; Sharp, Veronika; Kissin, Eugene Y
Abstract: Background: The effectiveness of interleukin-6 inhibitors (IL-6i) in ameliorating coronavirus disease 2019 (COVID-19) remains uncertain. Methods: We analyzed data for patients aged ≥18 years admitted with a positive severe acute respiratory syndrome coronavirus 2 polymerase chain reaction test at 4 safety-net hospital systems with diverse populations and high rates of medical comorbidities in 3 US regions. We used inverse probability of treatment weighting via machine learning for confounding adjustment by demographics, comorbidities, and disease severity markers. We estimated the average treatment effect, the odds of IL-6i effect on in-hospital mortality from COVID-19, using a logistic marginal structural model. Results: Of 516 patients, 104 (20.1%) received IL-6i. Estimate of the average treatment effect adjusted for confounders suggested a 37% reduction in odds of in-hospital mortality in those who received IL-6i compared with those who did not, although the confidence interval included the null value of 1 (odds ratio = 0.63; 95% confidence interval, .29–1.38). A sensitivity analysis suggested that potential unmeasured confounding would require a minimum odds ratio of 2.55 to nullify our estimated IL-6i effect size. Conclusions: Despite low precision, our findings suggested a relatively large effect size of IL-6i in reducing the odds of COVID-19–related in-hospital mortality. Abstract : Data from 516 patients at 4 US hospital systems of whom 20.1% received IL-6i suggests a 37% reduction in the odds of in-hospital mortality in those who received IL-6i (odds ratio = 0.63; 95% CI, .29–1.38).